1986
DOI: 10.1002/anie.198609171
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐Onio‐Substituted Quinones as Strong Electron Acceptors

Abstract: The bis‐ and tetrakispyridino‐substituted quinones 1 and 2 are stronger oxidizing agents than the known neutral systems p‐chloranil 3 and 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ). The first reduction potential of 2 is + 0.73 V (vs. Ag/AgCl)! The new oxidizing agents 1 and 2 are also interesting preparatively, because they are readily obtainable from p‐chloranil 3 and the transmaination reagent 4 and are insoluble in conventional aprotic solvents for all oxidation stages (which permits simple workup).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Furthermore, such a process should not be very difficult, as Weiss et al have shown that onio substitution dramatically increases the electron affinity of a given substance. [14] To test this hypothesis, and knowing that ylide 2 a featuring the very basic tris(dimethylamino)phosphine is stable, [8] we prepared the phosphonio-substituted aldiminium salt 1 a and reduced it with potassium metal (Scheme 3). The reaction was carried out in tetrahydrofuran at À50 8C.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, such a process should not be very difficult, as Weiss et al have shown that onio substitution dramatically increases the electron affinity of a given substance. [14] To test this hypothesis, and knowing that ylide 2 a featuring the very basic tris(dimethylamino)phosphine is stable, [8] we prepared the phosphonio-substituted aldiminium salt 1 a and reduced it with potassium metal (Scheme 3). The reaction was carried out in tetrahydrofuran at À50 8C.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption is backed by ample literature evidence that, unlike easily reduced 4,4′-bipyridinium derivatives, 5 , 30 , 31 DMAP + -polysubstituted arenes and quinones undergo reductions at far more negative voltages and that these reductions are often irreversible in nature. 32 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that these conclusions were reached under the assumption that the pyridinium groups themselves do not undergo reduction processes at these potentials. This assumption is backed by ample literature evidence that, unlike easily reduced 4,4′-bipyridinium derivatives, ,, DMAP + -polysubstituted arenes and quinones undergo reductions at far more negative voltages and that these reductions are often irreversible in nature. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding the use of transition-metal catalysts is important because such metals can contaminate the resultant polymers as an insoluble residue that can adversely affect performance when the polymers are used in electronic devices. S N Ar reactions using thiolates, aryloxides, and pyridine derivatives as nucleophiles have been used to fabricate functional small molecules and polymeric materials. However, the use of S N Ar reactions for modifying the main chain of conjugated polymers, again, remains rare. ,, …”
Section: Introductionmentioning
confidence: 99%